English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

1 answers

Look at each modulus separately:
a^13 = (a²)^6 *a = a(mod 3),
because a² = 1(mod 3) for any a by Fermat's
little theorem.
a^13 = (a^6)² *a = a(mod 7),
because a^6 = 1(mod 7), by Fermat's
little theorem.
Finally, a^13 = a(mod 13), again by Fermat's
little theorem.
So, by the Chinese remainder theorem,
a^13 = a(mod 3*7*13) for all a.

2007-04-11 06:54:00 · answer #1 · answered by steiner1745 7 · 1 0

fedest.com, questions and answers